Home-based digital exercise versus hospital physiotherapy for plantar fasciitis: a propensity-score-matched retrospective cohort study with dual-perspective cost-utility evaluation - Wenbo Xu; Lufeng Yao; Haigang Wang; Chenqin Xu; Pinpin He; Yi Zhang; Jiasong Pan; Shengdi Lu; Lei Huang (Journal of Rehabilitation Medicine, 2026)
Objective: To compare the clinical effectiveness and cost-effectiveness of a 12-week home-based digital exercise programme with 12-week hospital-supervised physiotherapy for plantar fasciitis in routine Chinese tertiary-hospital care. Design: Single-centre retrospective cohort study with 1:2 propensity-score matching on 13 baseline covariates. Subjects/Patients: 587 adults with a clinician-confirmed diagnosis of plantar fasciitis treated in 2022–2024 were matched. Methods: The primary outcome was first-step morning pain at 3 months on a 0–10 numeric rating scale (non-inferiority margin 1.3 points; sensitivity margins 0.9 and 1.9). A 12-month cost–utility analysis took payer and societal perspectives. Results: The adjusted mean difference was −0.63 points (95% confidence interval −0.92 to −0.35; p < 0.001), non-inferior against all 3 margins (E-value 2.84). Incremental payer cost was −¥4,920 (−US$684), incremental societal cost −¥7,008 (−US$974), and incremental quality-adjusted life-years +0.011, with dominance in 96.7% of bootstrap replications. Conclusion: Home-based digital exercise was non-inferior for 3-month first-step pain and less costly from both perspectives. Matching left 12 of 13 covariates imbalanced and only 6.3% of screened patients were eligible, so residual confounding and selection bias are likely. These observational findings are provisional and require confirmation in a pragmatic multicentre randomized controlled trial before informing reimbursement.